Trends and disparities in inflammatory bowel disease and cardiovascular disease-related mortality in the United States from 1999 to 2023: A CDC WONDER analysis - Syed Anjum Gardezi; Nakul Sachdeva; Insiya Mohammed Rampurawala; Akalanka Ranasinghe; Muhammad Umair Shehzad; Kieran Gill; Raheel Qureshi; Ashish Gupta; Ali Hasan; Muzammil Farhan; Azeem Hassan; Eeshal Zulfiqar; et al. (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Individuals with inflammatory Bowel Disease (IBD) may face an increased risk of cardiovascular disease (CVD) due to chronic systemic inflammation and vascular dysfunction. While advancements in treatment have improved IBD management, its impact on cardiovascular mortality remains unclear. This study aims to analyze trends in IBD- and CVD-related mortality in the U.S. from 1999 to 2023, identifying high-risk populations based on age, sex, race, and geography. Methods: Mortality data for individuals aged 25 years and older from 1999 to 2023 were obtained from the CDC WONDER database. Crude mortality rates (CMRs) and age-adjusted mortality rates (AAMRs) per 100,000 persons were calculated. Temporal trends were assessed using Joinpoint regression analysis to estimate the annual percent change (APC) and average annual percent change (AAPC) in mortality rates. Results: Between 1999 and 2023, a total of 41,635 deaths were identified related to IBD and CVD among adults aged 25 years and older. The overall AAMR remained relatively stable from 1999 to 2018 before increasing sharply from 0.67 in 2018 to 1.03 in 2021 [APC: 15.63∗ (95 % CI: 11.66, 17.91); p = 0.0004], after which it plateaued through 2023. Males consistently exhibited higher AAMRs than females throughout the study period (Males: 1.10 vs. Females: 0.90 in 2023). When stratified by race, the highest AAMR was observed in NH White populations, followed by NH Black or African American individuals (1.21 vs. 0.64 in 2023). Regionally, the highest mortality was observed in the West, followed by the Midwest, the Northeast, and lastly, the South (AAMR of 1.02, 1.08, 0.87, and 0.97, respectively, in 2023). Rural areas (0.74) exhibited consistently higher AAMRs than urban areas (0.69) from 1999 to 2020. Mortality rates increased with age, with the highest burden observed in individuals aged 85 years and older. Conclusion: IBD- and CVD-related mortality has risen in the U.S., with the highest burden among males, NH White individuals, and older adults. Targeted interventions and enhanced cardiovascular screening are needed to reduce mortality in high-risk populations.